Acts of Gaiety : LGBT Performance and the Politics of Pleasure - Warner, Sara (Book collections on Project MUSE., 2013)
"The book mines the archives of lesbian-feminist activism of the 1960s-70s, highlighting the outrageous gaiety that lay at the center of the social and theatrical performances of the era and uncovering original documents long thought to be lost. Juxtaposing historical figures such as Valerie Solanas and Jill Johnston with more recent performers and activists (including Hothead Paisan, Bitch & Animal, and the Five Lesbian Brothers), Warner shows how reclaiming this largely discarded and disavowed past elucidates possibilities for being and belonging."--Publisher